Source Code Plagiarism Detection Method Using Protégé Built Ontologies - Ion SMEUREANU; Bogdan IANCU (Informatică economică, 2013)
Software plagiarism is a growing and serious problem that affects computer science universities in particular and the quality of education in general. More and more students tend to copy their thesis’s software from older theses or internet databases. Checking source codes manually, to detect if they are similar or the same, is a laborious and time consuming job, maybe even impossible due to existence of large digital repositories. Ontology is a way of describing a document’s semantic, so it can be easily used for source code files too. OWL Web Ontology Language could find its applicability in describing both vocabulary and taxonomy of a programming language source code. SPARQL is a query language based on SQL that extracts saved or deducted information from ontologies. Our paper proposes a source code plagiarism detection method, based on ontologies created using Protégé editor, which can be applied in scanning students' theses' software source code.